Alkynyl Coinage Metal Clusters and Complexes–Syntheses, Structures, and Strategies. Issue 30 (24th March 2018) - Gupta, Arvind Kumar; Orthaber, Andreas
Abstract: In this Concept we discuss how the chemistry of coinage metal complexes based on alkynyl ligands has developed over the past decades. The rich coordination of alkynyl, that exhibit both η 1 (end‐on) and η 2 (side on) modes, includes non‐bridged systems, as well as bridging of up to four (or six) metal centres. Resulting metal clusters often exhibit highly regular structures and typical coordination motifs forming fascinating assemblies exploiting this versatile coordination. Metallophilic interactions are often an important driving force for the formation of large clusters. In addition, the use of co‐ligands as well the possibility to encapsulate counter ions greatly increases the chemical and structural diversity. Herein we attempt to summarize and highlight design principles towards multinuclear homo and hetero‐bi‐metallic coinage metal clusters of alkynyl ligands. Abstract : Coin toss : Syntheses, structural traits and properties of alkynyl coinage metals clusters are discussed and compared. Concepts and synthetic strategies are highlighted.